1999
DOI: 10.1038/sj.pcan.4500326
|View full text |Cite
|
Sign up to set email alerts
|

Transrectal ultrasound imaging of the prostate: review and perspectives of recent developments

Abstract: We present a critical review of the recent literature and discuss the development and prospective view of the evaluations of transrectal ultrasound with regard to prostate malignancy. We illustrate this with personal experiences. Material and Methods: Based on a critical evaluation of clinical data we address the apparent shortcoming of greyscale transrectal ultrasonography in the assessment of prostate cancer. New developments and future possibilities are also discussed.Evaluation of the value of greyscale tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 51 publications
0
2
0
1
Order By: Relevance
“…However, decades of clinical experience have shown that PSA is not ideal in terms of specificity, often leading to either overdiagnosis or overtreatment (4)(5)(6). Prostate biopsy is the most valuable method in the diagnosis of PCa (7,8). Although preoperative preparation is actively improved, hemospermia, hematuria, and urinary tract infection are still the main adverse effects (9).…”
Section: Introductionmentioning
confidence: 99%
“…However, decades of clinical experience have shown that PSA is not ideal in terms of specificity, often leading to either overdiagnosis or overtreatment (4)(5)(6). Prostate biopsy is the most valuable method in the diagnosis of PCa (7,8). Although preoperative preparation is actively improved, hemospermia, hematuria, and urinary tract infection are still the main adverse effects (9).…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with the characterization of papillary carcinomas as hypervascular formulated by other authors. 12 The resistance index, resistance expression or vascular impedance has to be taken into account, which suggests that, unlike in other organs, 13 in the thyroid gland is not possible for vascular resistance parameters to be correlated with the type of neoformation. 8 The fact of lower vascularization being found in papillary cancer might explain the low tendency towards hematogenous metastasis in this type of tumors, as well as their slow growth, given the direct relationship between angiogenesis and metastatic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Estos resultados concuerdan con la catalogación de los carcinomas papilares como hipervasculares que han formulado otros autores. 12 Hay que tener en cuenta el índice de resistencia, expresión de la resistencia o impedancia vascular, de lo cual se deduce que en la tiroides, a diferencia de lo observado en otros órganos, 13 no es posible correlacionar los parámetros de resistencia vascular con el tipo de neoformación. 8 El hecho de encontrar menor vascularización en los cánceres papilares podría explicar la escasa tendencia a la metástasis vía hemática de este tipo de tumores, así como su lento crecimiento, dada la relación directa entre angiogénesis y capacidad metastásica.…”
Section: Discussionunclassified